A relação entre a percepção dos colaboradores de uma instituição financeira sobre a remuneração estratégica e a virtuosidade organizacional - Machado Filho, João Francisco Rodrigues (2018)
Brazil's financial sector has a great importance in the national economy, and the banking sector is the most representative in this sector. Considering the relevance of the organizations of this segment, it is of great value to study their concepts and strategies, seeking greater efficiency and competitiveness. One of several ways to achieve these goals is through the motivation of the organization's employees, which involves strategic compensation and organizational virtuousness. The objective of this study was to investigate the perception about strategic remuneration and organizational virtuousness and its possible relationship, with employees of a financial organization located in the state of Paraná. Through a structured questionnaire, adapted from Rego, Ribeiro and Cunha (2010) translation of Cameron, Bright and Caza (2004) questionnaire and Reis Neto (2004) questionnaire, a quantitative research was conducted whose analysis of the answers led to the conclusion that the employees of the organization in question have a favorable view of the compensation system, and find virtuousness in the organization. The relationship between the perception of strategic remuneration and organizational virtuousness was measured using Pearson's correlation coefficient, resulting in a significant positive relationship between the two.